Overview on Echinococcosis - Derbel, Fethi; Braiki, Meriem (Infectious Diseases, 2020)
We are very pleased to present this book dealing with echinococcosis. The chapters of this book are written by surgeons, radiologists, and parasitologists from different hospitals in several countries as Tunisia, Turkey, Indonesia, Nigeria, Romania, Chile and Iraq. This book is intended for clinicians, radiologists, internists, and surgeons involved in the management of patients with echinococcosis.